The collected stories of Lydia Davis. - Davis, Lydia, 1947- (New York : Farrar, Straus and Giroux, 2009)
Lydia Davis is one of our most original and influential writers, a storyteller celebrated for her emotional acuity, her formal inventiveness, and her ability to capture the mind in overdrive. She has been called "an American virtuoso of the short story form" (Salon.com) and "one of the quiet giants ... of American fiction" (Los Angeles Times Book Review). This volume contains all her stories to date, from the acclaimed Break it Down (1986) to the 2007 National Book Award finalist Varieties of Disturbance. - Cover flap.
A single-volume compilation of the National Book Award finalist's short stories includes "Break it Down" and "Varieties of Disturbance."
Varieties of disturbance (2007). A man from her past -- Dog and me -- Enlightened -- The good taste contest -- Collaboration with fly -- Kafka cooks dinner -- Tropical storm -- Good Times -- Idea for a short documentary film -- Forbidden subjects -- Two types -- The senses -- Grammar questions -- Hand -- The caterpillar -- Child care -- We miss you: a study of get-well letters from a class of fourth-graders -- Passing wind -- Television -- Jane and the cane -- Getting to know your body -- Absentminded -- Southward bound, reads Worstward Ho -- The walk -- Varieties of disturbance -- Lonely -- Mrs. D and her maids -- 20 sculptures in one hour -- Nietzsche -- What you learn about the baby -- Her mother's mother -- How it is done -- Insomnia -- Burning family members -- The way to perfection -- The fellowship -- Helen and Vi: a study in health and vitality -- Reducing expenses -- Mother's reaction to my travel plans -- For sixty cents -- How shall I mourn them? -- A strange impulse -- How she could not drive -- Suddenly afraid -- Getting better -- Head, heart -- The strangers -- The busy road -- Order -- The fly -- Traveling with mother -- Index entry -- My son -- Example of the continuing past tense in a hotel room -- Cape Cod diary -- Almost over: what's the word? -- A different man.
A New York Times Book Review Editor's Choice; A Los Angeles Times Fiction Favorite for 2009; A San Francisco Chronicle Best Book of 2009.
NEW
Keywords: Short stories, American -- 21st century; Short stories, American -- 21st century; Short stories, American; 2000-2099; Short stories; short stories; Short stories; Short stories; Short stories; Nouvelles